The Effect of Stretch Goals on Destructive Leadership and Counterproductive Work Behavior in Indonesian State-Owned-Enterprises - Diah Retno Wulandaru; Wakhid Slamet Ciptono; Ely Susanto (Journal of Leadership in Organizations, 2022)
Introduction/Main Objectives: This study aims to examine the effect of stretch goals on destructive leadership with burnout as the mediating variable and then the effect of destructive leadership on counterproductive work behavior of employees with psychological capital as a moderating variable.  Background Problems: The phenomenon of irregularities that occur in SOE in Indonesia is interesting to study. Deviations committed by SOE leaders in Indonesia include fraud, gratification, and data manipulation. The increase in the number of irregularities has a negative effect on organizational performance because it causes several counterproductive work behaviors in employees.  Novelty: Empirical research on destructive leadership is still rare because previous research has focused only on the conceptual side. Research Methods: The design of this study used a survey with a questionnaire completed by 724 respondents who were leaders and employees. The hypothesis testing used Structural Equation Modeling (SEM).  Finding/Results: The findings of this study show a positive influence of stretch goals on burnout and a positive influence of stretch goals on destructive leadership, but burnout has no mediating role in the effect of stretch goals on destructive leadership. There is no effect of perceived destructive leadership on employees’ counterproductive work behavior, but psychological capital has a moderating role in the effect of perceived destructive leadership on employees’ counterproductive work behavior. Conclusion: The practical implication of this study is that a stretch goal that is not balanced with resources can cause individuals to behave destructively even though they are at a managerial level.